Absorption, metabolism and excretion of [14C]omarigliptin, a once-weekly DPP-4 inhibitor, in humans. (3rd June 2018) - Xu, Shiyao; Tatosian, Dan; Mcintosh, Ian; Caceres, Maria; Matthews, Catherine; Samuel, Koppara; Selverian, Diana; Kumar, Sanjeev; Kauh, Eunkyung
Abstract: 1. Omarigliptin (MARIZEV®) is a once-weekly DPP-4 inhibitor approved in Japan for the treatment of type 2 diabetes. The objective of this study was to investigate the absorption, metabolism and excretion of omarigliptin in humans. 2. Six healthy subjects received a single oral dose of 25  mg (2.1 μCi) [ 14  C]omarigliptin. Blood, plasma, urine and fecal samples were collected at various intervals for up to 20  days post-dose. Radioactivity levels in excreta and plasma/blood samples were determined by accelerator mass spectrometry (AMS). 3. [ 14  C]Omarigliptin was rapidly absorbed, with peak plasma concentrations observed at 0.5–2  h post-dose. The majority of the radioactivity was recovered in urine (∼74.4% of the dose), with less recovered in feces (∼3.4%), suggesting the compound was well absorbed. 4. Omarigliptin was the major component in urine (∼89% of the urinary radioactivity), indicating renal excretion of the unchanged drug as the primary clearance mechanism. Omarigliptin accounted for almost all the circulating radioactivity in plasma, with no major metabolites detected. 5. The predominantly renal elimination pathway, combined with the fact that omarigliptin is not a substrate of key drug transporters, suggest omarigliptin is unlikely to be subject to pharmacokinetic drug-drug interactions with other commonly prescribed agents.